Hazard/threat identification: Using functional resonance analysis method in conjunction with the Anticipatory Failure Determination method. (August 2017) - Jensen, Anders; Aven, Terje
An essential part of risk management is to identify possible harmful events. A number of approaches have been suggested for this purpose, including the Anticipatory Failure Determination method. The fundamental idea of Anticipatory Failure Determination is that revealing harmful events is fundamentally a creative act, and, instead of searching for possible harmful events; the strategy is rather to invent them using different kinds of creativity methods. This article addresses hazard/threat identification for complex systems, that is, systems which do not allow for accurate prediction models of the system based on knowing the specific functions and states of its individual components. Hazard/threat identification for such systems is challenging, as traditional cause and effect relationships and linear reasoning do not work. However, models and frameworks exist for analyzing such systems, the functional resonance analysis method being perhaps the most established approach. The purpose of this article is to present a new hazard/threat identification method combining Anticipatory Failure Determination and functional resonance analysis method. The method allows for using creative methods to invent potential hazards and threats in complex systems. We illustrate the method with an example.